Vision feedback on freeform-shaped structure for 3D printing - Quah, Noel Tan Kai (Nanyang Technological University, 2024)
In Singapore, there is an increasing need for independence in manpower within the Building and Construction (B&C) Industry. The current construction approach in Singapore’s high density urban landscape is the use of Prefabricated Prefinished Volumetric Construction (PPVC), where 3-dimensional modules with completed finishes, fixtures, and fittings are fabricated in a decentralised facility prior to its delivery and designated on-site installation. This construction method has benefited the populous with reduced environmental pollutants and reduced reliance to on-site personnel, while lowering exposure to construction site health hazards. Moreover, smaller module production permits improved productivity, quality control, and customizability.